Pengaruh Lari Cepat 30 Meter terhadap Kemampuan Tendangan Nare Chagi pada Atlet Taekwondo Junior Kabupaten Kotabaru - Persada, Tahta Syam Utama; Mashud, Mashud; Kahri, Ma’ruful (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2023)
This study aims to determine the effect of 30-meter sprint training on Nare Chagi's kick speed. The research was carried out at the Kotabaru Regency Dojang, managed directly by the Kotabaru Regency Taekwondo Management. This research was required to be completed in one month, August-September 2023. This research used an experimental method. The research sample was 30 POPDA athletes. The research results showed that the 30-meter running exercise influenced the increase in Nare Chagi's kick speed, with an increase in the experimental group from 0.42 to 0.89 or the average number of kicks increasing by 0.47. 30 meter running training can significantly increase the speed of the Nare Chagi kick by carrying out a T-test with the result of a Sig-t value of 0.02 < 0.05 HO Rejected and H1 Accepted. In conclusion, there is a significant influence between 30M speed running and nare chagi kick speed. Keywords TA30 Meter Fast Run, Nare Chagi, Taekwondo, Vertical Jump